Augmentation of distillate yield in "V"-type inclined wick solar still with cotton gauze cooling under regenerative effect. Issue 1 (31st December 2016) - Suneesh, P.U.; Paul, John; Jayaprakash, R.; Kumar, Sanjay; Denkenberger, David
Abstract: Water flowing over bare glass is not evenly distributed over the width of the glass cover. Effective temperature reduction in the glass cover is not possible in this case. Thin cotton gauze is used over the glass cover to solve this problem. The amount of water required to cool the glass cover is low and the flowing water is collected and fed into a hot water reservoir. Water from the hot water reservoir is directed to the wick absorber by a drip valve. The system was tested in two ways (i) regenerative effect with cotton gauze (ii) regenerative effect without cotton gauze. The inclined wick absorber ensures that the surface is always wet due to capillary action and there were no dry spots. Excess flow in the wick absorber is pumped back to the hot water reservoir. Due to low thermal inertia of the wick and regenerative effect, the system has quick start-up times, as well as higher operating temperatures. This resulted in higher distillate yield than simple solar stills. Since the hot water reservoir remained warm enough during the night hours, a reasonable amount of nocturnal distillate output was also obtained. Optimum inclination of the wick absorber was found to be 20° and mass flow rate through the wick absorber was 200 ml/minute. The system with cotton gauze produced distillate yield of 6, 300 ml/m 2 whereas the system without cotton gauze produced distillate yield of 5, 600 ml/m 2 .